Sustainable business development vision under the covid-19 pandemic - Nataliya Antonyuk; Iryna Plikus; Mohammad Jammal (Health Economics and Management Review)
This article considers the issues of forming sustainable business development strategies in the context of the COVID-19 pandemic. The authors noted that the COVID-19 pandemic significantly affected the business environment, changing each country's economy's priorities and principles of functioning. The study's main goal is to analyze the impact of quarantine measures and the pandemic on sustainable business development. The article examines the positive and negative COVID-19 influence on economic development. The methodological basis of this study is a systematic literature review using international scientific databases. For determining the scientists' and the business interest in the studied issue, Google Trends and Google Ngram Viewer tools were used. The authors used a systematic approach, abstract-logical and structural-dynamic analysis to determine trends in entrepreneurial activity. This paper presents the findings in shifting prioritize business skills for future development. The obtained results showed that individual professional and personal development became more important compared to communication skills. The authors identified the negative pandemic consequences such as social stratification and significant psycho-emotional pressure affecting socio-economic development. In turn, there is a need to quickly adapt to rapid changes, especially in the professional sphere was emphasized. The authors noted the inevitable digitalization process, which requires psychological readiness, stress resistance, cognitive flexibility, and emotional maturity. The obtained results allowed identifying the priorities of sustainable business development and areas of psychological support for private entrepreneurship in Ukraine. Thus, the formation of strategies for sustainable economic development in Ukraine should be based on business digitalization, adaptation to new business conditions, the acquisition of modern skills, reducing economic stratification of society, and reducing psychological stress. The study findings could be used in devising the regional development strategy to ensure a sustainable and efficient business environment. Moreover, the obtained results could be useful for the entrepreneurs to ensure personal development and get the desired level of profit while minimizing the business risks.